Special Education Right and the Disability Features of Psychiatric Disabled Children who at Risk for Child Abuse - Kaya, Ahsen; Meral, Orhan; Güler, Hülya; Aktaş, Ekin Özgür (The Bulletin of Legal Medicine, 2015)
Aim: Disabled children are a risky group for child abuse, while they mostly cannot predict the outcomes of the results of their behaviors and also they are insufficient in directing their behaviors, and cannot sift and know right from wrong. In this study, it was aimed to draw attention to the causes of disability and the disability ratios of the children with psychiatric disabilities who are at risk for child abuse. Materials and methods: With this regard, 2839 reports belong to children under 18, those were prepared between 01 January, 2011 and 30 June, 2013 by Disabilities Health Board of the Hospital, were examined and 2103 of them included children with psychiatric disabilities were analyzed retrospectively. Data were evaluated with SPSS (version 18.0) statistical program. Results: 1432 (68.1%) of the subjects were male, 671 (31.9%) were female, and the mean age was 6.7±4.3. The most common diagnosis for the subjects (n=911) was mild mental retardation. The first mostly stated cause of application in the reports was to have special education (95.3%). Conclusion: Special education right, which is one of the most important social rights for children with psychiatric disabilities, is offered free of charge with his/her disability report. The state providing this right free of charge is an important step towards the protection of the children from abuse. Moreover, special education right being ranked as the first among the reasons for application to Disability Report shows that families are contributing to the protect their children from abuse -intentionally or unintentionally.